Needs Assessment for Interactive Digital SOP Development in Vocational Culinary Education - Efrina Efrina; Mahdiyah Mahdiyah; Alvina Fadila Maulida (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Vocational education requires students to master practical and industry-relevant skills, particularly in laboratory-based fields such as culinary science and food technology. However, many Indonesian vocational programs still rely on instructor-led demonstrations and provide limited access to structured or digital Standard Operating Procedures (SOPs), which may reduce students’ confidence, independence, and accuracy in operating advanced instruments. Objective: This study aims to identify students’ needs for interactive digital SOPs to support self-directed learning and improve competence in operating laboratory instruments, particularly the Texture Profile Analyzer (TPA) and VolScan Profiler. Methods: A mixed-methods needs assessment was conducted involving 40 culinary students. Data were collected through structured questionnaires and open-ended responses to explore laboratory experience, instrument familiarity, perceived barriers, and preferred learning media. Results: The findings showed 75% of students rarely participated in laboratory activities, and 88% relied entirely on instructor guidance. Only 45% had experience using the TPA, while only 5% had used the VolScan Profiler. In addition, 50% reported the absence of written SOPs. The main barriers were equipment-related technical issues (42%), limited operational knowledge (30%), and unclear instructions (15%). Most students preferred video tutorials (83%), supported by simplified language, contextual explanations, QR code-linked manuals, and digital integration. Conclusion: The study highlights the need to transform static SOPs into interactive, learner-centered digital formats aligned with Outcome-Based Education (OBE), digital literacy development, and the Merdeka Belajar Kampus Merdeka (MBKM) framework. These findings provide a foundation for developing digital SOPs that improve procedural understanding, independent learning, and laboratory competence among vocational culinary students.